2022
DOI: 10.1007/s12144-022-03445-9
|View full text |Cite
|
Sign up to set email alerts
|

Parental psychological control and adolescents depression during the COVID-19 pandemic: the mediating and moderating effect of self-concept clarity and mindfulness

Abstract: During the COVID-19 pandemic, the mental health state of adolescents had caused widespread concern, especially the various problems caused by the relationship between adolescents and their parents in the long isolation at home. Based on the mindfulness reperceiving model and Rogers's Self-theory, this study aimed to explore the roles of adolescents' self-concept clarity and mindfulness level in the relationship between parental psychological control and adolescent depression. A total of 1,100 junior high schoo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 70 publications
0
4
0
Order By: Relevance
“…The study used a 13-item version of the BDI compiled by American psychologist Beck AT (1974), revised by Zheng et al [ 55 ], tested with good reliability and validity, and has been widely used in Chinese adolescents [ 27 , 56 ]. Each item was scored with a 4-point score ranging from 0 to 3 (no such symptoms = 0; mild = 1; moderate = 2; severe = 3), with higher scores indicating higher depressive proneness and lower scores indicating lower depressive proneness.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…The study used a 13-item version of the BDI compiled by American psychologist Beck AT (1974), revised by Zheng et al [ 55 ], tested with good reliability and validity, and has been widely used in Chinese adolescents [ 27 , 56 ]. Each item was scored with a 4-point score ranging from 0 to 3 (no such symptoms = 0; mild = 1; moderate = 2; severe = 3), with higher scores indicating higher depressive proneness and lower scores indicating lower depressive proneness.…”
Section: Methodsmentioning
confidence: 99%
“…It has been established that there is a significant correlation between cognitive failures and depression, and individuals who experience more cognitive failures have a higher level of depression [ 25 , 26 ]. Furthermore, repeated cognitive failures tend to cause negative self-evaluations [ 27 ], which can increase the risk of depression [ 28 ]. Conversely, the cognitive functions of depressed individuals, including processing speed, logical reasoning, attention, and executive function, will decline to varying degrees, which are also essential factors in triggering cognitive failures [ 29 ].…”
Section: Introductionmentioning
confidence: 99%
“…Moreover, several studies have indicated that parental psychological control can in uence mental health through intermediary variables such as basic psychological needs, emotional regulation, and selfconcept [20][21][22]. According to the theory of individual-situation interaction, external situational factors can impact mental health by affecting individual traits [7].…”
Section: Role Of Psychological Resilience In the Relationship Between...mentioning
confidence: 99%
“…For example, family cohesion and parent-child relationships were confirmed to be associated with stress consequences during COVID-19 pandemic (Ye, Y. et al, 2022c;Zeng et al, 2021). Around 10% of college students had persistent and/or developed new mental health problems during the pandemic and low quality of family function were significant predictors of lower mental health (Li et al, 2021b(Li et al, , 2022. However, research focusing on risk factors of college student's mental health during COVID-19, especially the role of family, were still limited (Al-Omiri et al, 2021;Marchetti et al, 2020).…”
Section: Introductionmentioning
confidence: 99%